Private tutoring when stakes are high: Insights from the transition from primary to secondary school in Germany. (March 2019) - Guill, Karin; Lintorf, Katrin
Highlights: A noteworthy number of students receive private tutoring, even in primary school. Tutoring is more likely in regions with high-stakes transitions between school stages. High aspirations combined with high-stakes transitions raise tutoring probability. The positive and negative potentials of a flexible education system are discussed. Abstract: Private supplementary tutoring is a widespread and controversial phenomenon. The pressure high-stakes exams put on students is often held responsible for high tutoring rates. Our study tested this hypothesis by using regional variance in Germany: Results from two of three large-scale studies give evidence that, in regions where the transition from primary to secondary school resembles high-stakes exams, the probability to attend private tutoring is higher than in other regions. Therefore, we discuss how a more flexible education system with different pathways to the same educational goal might obviate the need for private tutoring and we consider this system's side-effects.